How to Develop Productive Skills with the Help of Critical Thinking Activities of B1 Level Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper explores the development of productive skills, namely speaking and writing, in B1 level learners through the integration of critical thinking activities. By incorporating critical thinking exercises into language learning activities, educators can enhance students' ability to express themselves effectively and think critically in the target language. The paper discusses various strategies and techniques that can be used to promote critical thinking skills in B1 level learners, such as analyzing and evaluating information, making connections between ideas, and synthesizing information to form coherent arguments. Additionally, the paper highlights the benefits of integrating critical thinking activities into language learning, including improved communication skills, increased engagement, and enhanced cognitive abilities. Overall, this paper aims to provide educators with practical insights and recommendations for developing productive skills in B1 level learners through the application of critical thinking activities..